Emergent surgical removal of a migrated left atrial appendage occluder. (29th January 2018) - El-Gabry, Mohamed; Shehada, Sharaf-Eldin; Wendt, Daniel; Mourad, Fanar
Abstract: Occlusion of the left atrial appendage (LAA) in patients with atrial fibrillation has become a standard therapy to prevent thromboembolic complications. We aim to present 3 cases of LAA occluder embolization after percutaneous WATCHMAN™ device implantation, which required emergent surgical retrieval. The device was dislocated in the left atrium, introducing LAA perforation and resulting in pericardial effusion and later tamponade in 1 patient who developed multiorgan failure and died 8 days postoperatively. Other patients were successfully operated and discharged. Hence, LAA occluder embolization may occur asymptomatically with immediate/late serious complications, which indicates emergent surgery.